2007
DOI: 10.1163/156854007782605592
|View full text |Cite
|
Sign up to set email alerts
|

Gammarus Izmirensis Sp. Nov., A New Species of Freshwater Amphipod from Turkey (Amphipoda, Gammaridae)

Abstract: A new species of freshwater amphipod, Gammarus izmirensis sp. nov., belonging to the Gammarus pulex-group, is described. Specimens have been collected from a stream in the Kemalpaşa district,İzmir province, western Anatolia. A detailed morphological description and illustrations of the new species are given. Differences between the new species and related species are discussed. RÉSUMÉUne nouvelle espèce d'amphipode d'eaux douces, Gammarus izmirensis sp. nov., appartenant au groupe Gammarus pulex, est décrite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The taxonomy of Gammarus remains unsatisfactory despite recent revisions of regional faunas (Karaman & Pinkster, 1977a, b, 1987; Hou, 2002) and many current taxonomic publications (Stock et al. , 1998; Özbek, 2007). The morphology‐based taxonomy of Gammarus requires investigation of numerous characters, and detailed morphological studies have shown that many variable traits are of limited utility because of phenotypic plasticity and ecological diversity (Pinkster, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomy of Gammarus remains unsatisfactory despite recent revisions of regional faunas (Karaman & Pinkster, 1977a, b, 1987; Hou, 2002) and many current taxonomic publications (Stock et al. , 1998; Özbek, 2007). The morphology‐based taxonomy of Gammarus requires investigation of numerous characters, and detailed morphological studies have shown that many variable traits are of limited utility because of phenotypic plasticity and ecological diversity (Pinkster, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Gammarus Fabricius, 1775, with more than 200 species, inhabits marine and freshwater environments; while most are epigean, some of them have been reported from caves and wells (Karaman & Pinkster, 1977a;Özbek et al, 2013). Species of this genus are distributed in the Holarctic and Palearctic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Özbek and Ustaoğlu, 2006;Karaman and Pinkster, 1977;Karaman, 1973;Ustaoğlu et. al., 2004;Duran, 2007;Özbek, 2007;Özbek and Topkara, 2007 etc. ), very little study has been issued the compositions of Gammarus spp.…”
Section: Introductionmentioning
confidence: 99%